Fitness-for-service of engineering structures with general metal loss - Lee, Qian Yu (2019)
Fitness-for-service (FFS) assessments are procedures that assess the fitness of deteriorated pressure equipment to continue running in operation. API 579-1/ASME FFS-1 is one standard which provides guidelines for FFS, covering different types of flaws and damages. This project examined the FFS assessment methods recommended by API 579-1/ASME FFS-1 for components suffering from general metal loss. A spreadsheet was then designed using Microsoft Excel to automate these assessment procedures, so that FFS assessment can be simplified. The spreadsheet was designed to be independently used and includes the necessary functions for FFS assessment of a wide range of common components. The spreadsheet was then tested by checking its results for two example problems against manual calculations, and it produced highly accurate results in both cases.